Detection of cervical spine fracture on computed radiography images a monitor resolution study. - Awan O; Safdar NM; Siddiqui KM; Moffitt R; Siegel EL; Awan, Omer; Safdar, Nabile M; Siddiqui, Khan M; Moffitt, Ryan; Siegel, Eliot L (Academic Radiology, 2011)
Rationale and Objectives: The purpose of this study was to evaluate the diagnostic accuracy of radiologists using monochrome medical-grade 5 megapixel (MP), 3 MP, 2 MP, and 1 MP displays for the detection of cervical fractures on cervical radiographs, while controlling factors such as luminance and ambient conditions. Materials and Methods: Institutional review board approval was obtained. Two hundred lateral cervical computed radiography images, 97 with fractures, were randomly displayed on 5-MP, 3-MP, 2-MP, or 1-MP liquid crystal displays (LCDs) for a total of 450 interpretations per display. These radiographs were presented in eight sessions, each with 25 radiographs, to nine readers. The reference standard for all cases was computed tomography. Ambient lighting, monitor luminance, and gamma were controlled throughout the study. Measures included receiver operator characteristic areas under the curve (AUC), sensitivity, specificity, and accuracy, mean elapsed time by display, and mean confidence level by display. One way analysis of variance was performed. Results were considered to be significant at an alpha level of 0.05. Results: AUCs were 0.76 (95% CI, 0.72-0.80) for the 1 MP, 0.80 (95% CI, 0.76-0.84) for the 2 MP, 0.77 (95% CI, 0.73-0.81) for the 3 MP, and 0.76 (95% CI, 0.72-0.80) for the 5 MP medical grade LCDs. There was no significant difference in the AUCs (P values between .0651 and .8693), confidence (P = .158), or interpretation times (P = .751). Conclusion: When controlling factors such as luminance and ambient light, a difference in accuracy in the detection of cervical fractures by resolution could not be detected when using medical-grade displays. Interpretation time and confidence were also not affected by resolution.